xylE functions as an efficient reporter gene in Streptomyces spp.: use for the study of galP1, a catabolite-controlled promoter. - Ingram, C (1989)
We describe the development of a convenient and sensitive reporter gene system for Streptomyces spp. based on the use of a promoterless copy of the xylE gene of Pseudomonas putida. The xylE gene product is a catechol dioxygenase, which converts the colorless substrate catechol to an intensely yellow hydroxymuconic semialdehyde. A promoterless copy of xylE was placed under the transcriptional control of galP1, a glucose-repressed and galactose-induced promoter from Streptomyces lividans, and its expression was examined in bacterial colonies on agar plates or in liquid cultures grown in the presence of glucose or galactose as the sole carbon source. On plates, colonies of bacteria grown on galactose turned bright yellow within a few minutes of being sprayed with a solution of catechol, whereas colonies on glucose-containing plates remained white or only slightly colored, even after extensive incubation. Activity of galP1-xylE fusions was conveniently measured in crude cell extracts with a simple colorimetric assay and was shown to faithfully reflect intracellular RNA levels, as determined by quantitative dot blots. Moreover, differences in expression levels of xylE fusions driven by mutant galP1 promoters were readily apparent in color reactions on plates. The properties of xylE as a reporter gene thus make it suitable not only for quantitatively monitoring expression of regulated promoters in Streptomyces spp. but also for recovering mutations that alter the expression levels of promoters of interest.